Vaccination Communication Efforts with Research and Extension in Kansas - Roberts, Del'Sha (My University, 2022)
Early in the COVID-19 pandemic, public health officials learned that people were hesitant of the COVID-19 vaccination because of misinformation, distrust in the medical and scientific community, and the politicization of vaccinations. Vaccination acceptance was a concern that prompted the Centers for Disease Control and Prevention (CDC) to fund 82 Extension systems to receive grant funding for vaccination education for COVID-19 and Influenza. This project aimed to increase vaccination uptake in Kansas by creating targeted relevant messaging for vaccination uptake by engaging in community events in Kansas. This was done by conducting vaccination communication activities at community events, producing informative written materials, and evaluating providers' and supporters’ experiences and perspectives of COVID-19 vaccine clinics. Our goal was to increase vaccination acceptance through our efforts. As the pandemic continued to unfold, our efforts had to evolve to ensure the messaging was relevant and met the need. The results of the campaign can be applied to future vaccination communication efforts.
Keywords: vaccination; uptake; COVID-19; hesitancy; public health; acceptance